Vitamin E as Adjuvant Treatment for Urinary Tract Infection in Girls with Acute Pyelonephritis (Iranian Journal of Kidney Diseases, 2015)
Introduction. Vitamin E is a fat-soluble vitamin that functions as an antioxidant. The aim of this study was to investigate the effects of vitamins E supplementation in combination with antibiotics for the treatment of girls with acute pyelonephritis. Materials and Methods. This double-blinded randomized controlled trial was conducted on 152 girls aged 5 to 12 years with a first acute pyelonephritis episode based on technetium Tc 99m dimercaptosuccinic acid (99mTc-DMSA). They were randomized to receive a 14-day treatment with only antibiotics (control group; n = 76) and 14-day treatment with supplements of vitamin E (intervention group; n = 76) in addition to the antibiotics. Patients' clinical symptoms were monitored for 14 days and urine culture was performed 3 to 4 days and 7 to 10 days after the start of the treatment and its completion, respectively. All of the girls once underwent DMSA scan 4 to 6 months after the treatment. Results. During the follow-up days, the mean frequency of fever (P = .01), urinary frequency (P = .001), urgency (P = .003), dribbling (P = .001), and urinary incontinence (P = .006) were significantly lower in the intervention group compared to the control group. There was no significant difference in the results of urine culture 3 to 4 days after the start of treatment (P = .16) and 7 to 10 days after its termination (P = .37). There was also no significant difference between the results of DMSA scan 4 to 6 months after the start of treatment (P = .31). Conclusions. Vitamin E supplementation has a significant effect in ameliorating sign and symptoms of UTI. However, further studies are recommended to confirm these findings.